2008
DOI: 10.1007/s00284-008-9188-7
|View full text |Cite
|
Sign up to set email alerts
|

Novel Light-Activated Antimicrobial Coatings Are Effective Against Surface-Deposited Staphylococcus aureus

Abstract: Aerosols constitute a major route of transmission for a wide range of infectious diseases in the hospital setting. The aim of this study was to determine the survival of Staphylococcus aureus on a light-activated antimicrobial coating. S. aureus suspended in phosphate-buffered saline (PBS), saliva, or horse serum was sprayed onto cellulose acetate coatings containing toluidine blue O and rose bengal and the survival of the organism on these surfaces was determined following 6 h of exposure to a 28-W domestic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 29 publications
0
45
0
Order By: Relevance
“…Thus, antimicrobial activities are the most important evaluation for SecA inhibitors. RB has been reported to possess antimicrobial activities against S. aureus [24, 25]. We determined the antimicrobial effect of the RB analogs against S. aureus , including three MRSA strains (N315, Mu3, and Mu50).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, antimicrobial activities are the most important evaluation for SecA inhibitors. RB has been reported to possess antimicrobial activities against S. aureus [24, 25]. We determined the antimicrobial effect of the RB analogs against S. aureus , including three MRSA strains (N315, Mu3, and Mu50).…”
Section: Resultsmentioning
confidence: 99%
“…Some hospitals in various countries have already introduced pieces of equipment made of antimicrobial materials. Moreover, results of relatively scarce, hitherto, research have confirmed the decrease in infections of this type in hospital units [29]. Introduction of this type of equipment into hospitals should be preceded by a careful analysis of the situation in a given facility, in departments of various types.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, the three satisfactory features are integrated into a single polymer, which is very different from the currently designed multifunctional antimicrobial systems that are composed of complicated systematic compositions. Although our newly established system shows lower antibacterial activity to gram-negative bacteria, in comparison to the considerably developed antimicrobial surfaces and silver-polymer systems, [28][29][30][31] it exhibits several conspicuous advantages. These include the aforementioned selective recognition, imaging, and killing of bacteria over mammalian cells; prominent dark toxicity toward gram-positive bacteria; short (6-10 min) and relatively mild white light irradiation that is benefi cial for cell-based systems (such as wound infections caused by pathogens); and the avoidance of heavy metal accumulation, which is environmentally friendly.…”
Section: Doi: 101002/adma201102850mentioning
confidence: 98%